Improving Vocabulary Mastery of Elementary School Students by Using Storytelling Strategy - Hany Noviya; Mirjam Anugerahwati (EDUCATIO: Journal of Education, 2021)
Vocabulary is the language resource for the students to construct a sentence. Despite the important role of vocabulary, studies about vocabulary teaching, especially for young learners, revealed that their vocabulary mastery was still unsatisfactory. The students at Class 5A SDN Lowokwaru 2 Malang also had similar problems. It was found out that there was a lack of a variety of teaching strategy which was interesting for elementary school students who are young learners. This current study was collaborative action research covering four stages: planning, implementing, observing, and reflecting. There were 34 students who participated in the current study. The study revealed that of storytelling strategy could improve the students’ vocabulary mastery. The average score of students’ vocabulary test at the end of Cycle 1 was 81.5. It indicated that 91.17% of the students had reached the criteria of success. The researcher did three stages in implementing storytelling strategy i.e. in pre-story stage, in-story, and post-story stage. Based on the research findings, the implementation of a storytelling strategy could improve the students' vocabulary mastery and participation in learning activities. It could be inferred that the storytelling strategy was successful in improving students’ vocabulary mastery.